2007
DOI: 10.1038/sj.leu.2404944
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nilotinib and imatinib inhibition of FMS receptor signaling, macrophage production and osteoclastogenesis

Abstract: References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…Expression of MOZ-TIF2 in different cell lines results in depletion of CBP from PML bodies and a strong reduction in overall cellular levels of CBP protein. 3,5 Failure to detect changes in the levels of CBP transcripts indicated that this was likely to be a posttranscriptional effect (data not shown). To explore the underlying mechanism, a stable cell line (U2Os-TRex) carrying an inducible MOZ-TIF2 expression vector 5 was cultured in the presence or absence of doxycycline and treated with a range of small molecule inhibitors of protease or proteasome activities.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 4 more Smart Citations
“…Expression of MOZ-TIF2 in different cell lines results in depletion of CBP from PML bodies and a strong reduction in overall cellular levels of CBP protein. 3,5 Failure to detect changes in the levels of CBP transcripts indicated that this was likely to be a posttranscriptional effect (data not shown). To explore the underlying mechanism, a stable cell line (U2Os-TRex) carrying an inducible MOZ-TIF2 expression vector 5 was cultured in the presence or absence of doxycycline and treated with a range of small molecule inhibitors of protease or proteasome activities.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…3,5 Failure to detect changes in the levels of CBP transcripts indicated that this was likely to be a posttranscriptional effect (data not shown). To explore the underlying mechanism, a stable cell line (U2Os-TRex) carrying an inducible MOZ-TIF2 expression vector 5 was cultured in the presence or absence of doxycycline and treated with a range of small molecule inhibitors of protease or proteasome activities. Western blot analysis on whole cell extracts revealed that, consistent with previous results, cells induced to express YFP-MOZ-TIF2 (Figure 1a; Lane 2), (but not YFP or YFP-MOZ-TIF2 DAD1 3 ), showed a strong depletion of CBP and p300 proteins (top and middle panels), in contrast to control proteins such as a-tubulin or b-actin (lower panel).…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 3 more Smart Citations